Polyglot - Mohd Azmi, Aisyah Madihah; Mohd Rizuhan, Najwa Nabilah; Mohammad Adli, Muhammad Danish Hakim; Abd Halim, Akmal Hamdi; Abdul Sai, Nurafiq Ahlami; Ismawi, Hidayatul Radziah (Malaysian Integrated Medical Professionals Association, 2022)
The IIUM MBBS SEMINAR SERIES are e-books based on Phase 1 Kulliyyah of Medicine, IIUM, MBBS student seminar presentations. As part of the curriculum, all students are required to present one seminar. Topics covered are varied and not necessarily related to medicine.